Kinetic study and model of fermentation parameters affected growth and xylitol production in bioreactor by Kluyveromyces marxianus ATCC 36,907 - Abdul Manaf, Shareena Fairuz; Indera Luthfi, Abdullah Amru; Tan, Jian Ping; Mohamed Abdul, Peer; Jamali, Nur Syakina (Springer, 2022)
Optimum conditions for xylitol production from xylose based on the reliable kinetic models of the fermentative performance are important to design lignocellulosic xylitol production. The model was validated by comparing the simulation results with experimental data in batch culture of Kluyveromyces marxianus ATCC 36,907 under various concentrations of initial substrate (36 to 122 g/L) and agitation speed of the impeller (200 to 500 rpm) in a 3.6-L bioreactor. The model suggested that the kinetics of K. marxianus ATCC 36,907 using a modified Monod equation was regulated by the effects of xylose concentrations and oxygen levels during the fermentation. Xylitol production appeared favorable with maximum yield of 0.43 g/g corresponded to kLa value of 29.9 h−1 with low microbial growth. Sensitivity analysis on the obtained model parameters showed that the maximum specific growth rates (µmax) and substrate consumption constant (KS) are the most influential model parameters for xylitol production.